2015
DOI: 10.1227/neu.0000000000000815
|View full text |Cite
|
Sign up to set email alerts
|

National Trends and In-hospital Complication Rates in More Than 1600 Hemispherectomies From 1988 to 2010

Abstract: This is the largest study to date examining hemispherectomy and associated in-hospital complication rates. This study supports early surgery in patients with medically intractable epilepsy and severe hemispheric disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…This rate is remarkably similar to the 56% rate of complications for hemispherectomies observed in the Nationwide Inpatient Sample (Vadera et al, 2015). …”
Section: Discussionsupporting
confidence: 81%
“…This rate is remarkably similar to the 56% rate of complications for hemispherectomies observed in the Nationwide Inpatient Sample (Vadera et al, 2015). …”
Section: Discussionsupporting
confidence: 81%
“…We defined surgical complication using secondary ICD-9-CM codes including stroke and hematoma (432.1, 997.00, 997.01, 997.02, 997.09, 998.11, 998.12), postoperative intracranial infections (320.0, 320.7, 320.81-320.9, 322.9, 998.51, 998.59), status epilepticus (345.3), hydrocephalus (331.3, 331.4), ventriculoperitoneal shunt placement (02.34), blood transfusion (99.01-99.09), postoperative mechanical ventilation (96.70-96.79), and meningitis (320-322, 326). 11 Common in-hospital complication variables included cardiac (997.1, 410), respiratory (518.4, 518.5, 518.81-518.84), renal/urinary (584 and 997.5), and thromboembolic (415, 415.11-415.19, 451.0-451.9). 12 Discharge disposition was dichotomized into "routine" and "adverse discharge," meaning any discharge other than routine (transfer to skilled nursing, intermediate care facility, short-term acute-care hospital, or home health care).…”
Section: Outcome Variablesmentioning
confidence: 99%
“…These surgeries are often performed on young children and are long, tedious surgeries, which often require blood transfusions. Vadera et al 11 utilized the NIS to identify 304 pediatric patients who underwent hemispherectomy between 1988 and 2010. They found that 56% of patients encountered a complication (42% related to surgery).…”
Section: Cause Of Readmissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…sensus arose around prophylactic antibiotics, the use of high-speed drills for bone opening, of nonresorbable material for bone flap closure, of head fixation, of the use of the surgical microscope, and of free bone flaps • On the other hand, many other issues such as the use of ECoG, drains, valproate withdrawal, and so on, remained controversial and should be studied in adequate randomized clinical trials • Further knowledge on these various technical issues might lead to increased standardization and lower costs in the future; these future studies might lead to definitive practice guidelines Pediatric epilepsy surgery has been performed with increasing frequency over the last 30 years in a growing target population. [1][2][3] This is related to increased public awareness that surgical treatment is possible, improved recognition of candidates for surgery, the wider availability of investigational tools (especially magnetic resonance imaging [MRI] and video-electroencephalography [EEG]), improvement in surgical techniques, and the appreciation that seizure cessation for some children may impact positively on cognitive and behavioral development. 4,5 As happens in many areas of surgery, surgical techniques vary between centers, although pediatric epilepsy surgery itself is not new.…”
mentioning
confidence: 99%